2019
DOI: 10.4236/jamp.2019.75077
|View full text |Cite
|
Sign up to set email alerts
|

An Elementary Study of Chaotic Behaviors in 1-D Maps

Abstract: In this article, we have discussed basic concepts of one-dimensional maps like Cubic map, Sine map and analyzed their chaotic behaviors in several senses in the unit interval. We have mainly focused on Orbit Analysis, Time Series Analysis, Lyapunov Exponent Analysis, Sensitivity to Initial Conditions, Bifurcation Diagram, Cobweb Diagram, Histogram, Mathematical Analysis by Newton's Iteration, Trajectories and Sensitivity to Numerical Inaccuracies of the said maps. We have tried to make decision about these men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[39][40][41] Dysfunction of osteoblasts could delay bone formation and cause a spectrum of diseases, such as osteoporosis and dwarfism. 17,42 Here, by combined deletions of IFT20 and WWTR1 in osteoblasts using OSX-Cre mice, we found for the first time that loss of IFT20 and WWTR1 in osteoblasts significantly increased MAT accumulation and reduced bone mass, showing a severe osteoporosislike phenotype in 12-week-old dKO mice. Mechanistically, we revealed that IFT20 and WWTR1 play essential roles in osteoblasts for controlling MAT and bone homeostasis via regulating the stability and expression of TβRII.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[39][40][41] Dysfunction of osteoblasts could delay bone formation and cause a spectrum of diseases, such as osteoporosis and dwarfism. 17,42 Here, by combined deletions of IFT20 and WWTR1 in osteoblasts using OSX-Cre mice, we found for the first time that loss of IFT20 and WWTR1 in osteoblasts significantly increased MAT accumulation and reduced bone mass, showing a severe osteoporosislike phenotype in 12-week-old dKO mice. Mechanistically, we revealed that IFT20 and WWTR1 play essential roles in osteoblasts for controlling MAT and bone homeostasis via regulating the stability and expression of TβRII.…”
Section: Discussionmentioning
confidence: 74%
“…15,16 Dysfunction of osteoblasts could result in various bone diseases, including osteoporosis. 17,18 Moreover, disruption of the balance between adipogenesis and osteogenesis has been reported to contribute to osteopenia accompanied by progressive marrow adiposity. Nevertheless, what signaling molecules or critical genes control the commitment and function of osteoprogenitor cells are still undiscovered.…”
Section: Introductionmentioning
confidence: 99%